Penciptaan Teater “Hikayat Cantoi”: Adaptasi dari Konsep Teater Tutur Aceh Adnan PM TOH - Sulaiman Juned (Dance and Theatre Review, 2020)
AbstractCreating the monologue theater is based on Teater Tutur Aceh, PM TOH. The author did not start from the saga script but wrote a monologue script entitled “Hikayat Cantoi” and was performed in Indonesian. The show combined the modern convention, especially in movement and blocking of actors on stage, setting (decoration), props, make-up, and clothing by using the wealth of the body as music (body percussion music), such as: pat the chest, thighs, stomach, and fingertips in the Seudati, Didong, and Guel dance. This work presents a character who has historical and psychological complexities. Cantoi, an Acehnese man who works as a teacher, is forced by the situation to become “Pak Turut” to save his soul. The author chose this imaginary character because in Aceh, the term for someone who is smart but looks stupid, and is called Cantoi. Between 1996-2003, Acehnese society experienced a cultural shift or change. It happens because of social interaction through the pressures that are experienced at any time. Changes in social behavior lead to the birth of ideology and the restructuring of people’s behavior.Keywords: creative process; monologue; speech theater; Adnan PM TOH; Acehnese locality